The Silk Road : A Very Short Introduction - Millward, James A., 1961- (Oxford, New York Oxford University Press, 2013)
This title presents a new look at an ancient subject: the silk road that linked China, India, Persia and the Mediterranean across the expanses of Central Asia. James A. Millward highlights unusual but important biological, technological, and cultural exchanges over the silk roads that stimulated development across Eurasia and underpin civilization in our modern, globalized world.
Include Index and Illustration
Keywords: Asia, Central -- Asia--Silk Road -- Eurasia